2010
DOI: 10.1021/jp106773y
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterned Polyvinyl Butyral Membrane for Acid−Base Diodes

Abstract: Until now, polyvinyl alcohol (PVA) gel cylinders have been used in electrolyte diodes as a connecting element between the acidic and alkaline reservoirs. In this paper, a new connecting element is reported: a breath figure templated polyvinyl butyral (PVB) membrane prepared with dip-coating from a dichloromethane solution of the polymer in a humid atmosphere. The procedure gives a 1.5-2 μm thick membrane with a hexagonal pattern, the average characteristic length of which is 1 μm. After an acidic etching, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…14,15 In the electrolyte diodes developed for analytical purposes, hydrogels are commonly utilized as connecting elements between the acidic and alkaline reservoirs. 16,17 Environmental-sensitive hydrogels are frequently used materials not only in chemistry and physics but also in biomedical applications, such as tissue engineering and drug delivery. 18,19 For those kinds of applications, the improvement of shear-thinning and self-healing properties together with a reduced response time is essential and may be tuned by changes in pH or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In the electrolyte diodes developed for analytical purposes, hydrogels are commonly utilized as connecting elements between the acidic and alkaline reservoirs. 16,17 Environmental-sensitive hydrogels are frequently used materials not only in chemistry and physics but also in biomedical applications, such as tissue engineering and drug delivery. 18,19 For those kinds of applications, the improvement of shear-thinning and self-healing properties together with a reduced response time is essential and may be tuned by changes in pH or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the slow time response of the diode when PVA gel cylinder is used as a connecting element, a much thinner (and faster) PVB membrane was developed [8]. It was observed that during periodic switching of voltage between forward and reverse modes, an overshoot (a local maximum followed by a local minimum) appears in the measured current, when PVA gel cylinder is used as connecting element.…”
Section: Motivation Of the Researchmentioning
confidence: 99%
“…Dip-coating is also an alternative methodology successfully employed to prepare regular arrays of micrometer pores [76,77]. As depicted in (iv), in this case, due to the vertical position of the glass slide and the liquid surface, the mechanism is slightly different.…”
Section: General Strategies: To Fabricate Porous Films By Bfsmentioning
confidence: 99%